La recuperación de los conocimientos ecológicos locales en una experiencia de educación indígena en México - Laura Priscila Tercero-Cruz (IdeAs)
In the nineties of the twentieth century, after the attempts of spanishization and forced integration, indigenous education in Mexico took a pedagogical turnaround. It opened the way to intercultural education and its own pedagogies. From that moment on, various educational experiences emerged based on the local knowledge of each native people, recovering the best of their historical, cultural and ecological knowledge. Through a brief systematization of ecological knowledge about the natural cycles (agricultural, related to traditional medicine, among others) based on the calendar of the Ñomndaa (Amuzgo) people, this paper describes the recovery of ecological knowledge as part of a pedagogical strategy of the Project “A School for Life” located in Xochistlahuaca, Guerrero, Mexico.